Talk that counts age, gender, and social class differences in discourse - Macaulay, Ronald K. S.; Oxford eBooks (Oxford : Oxford University Press, 2005)
Here the author provides a new way of examining sociolinguistic variation. Using a sample from 33 speakers of English in Glasgow, he offers a new methodological paradigm to an audience of sociolinguists and others concerned with discourse analysis.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Scots language -- Social aspects -- Scotland -- Glasgow; Scots language -- Spoken Scots -- Scotland -- Glasgow; Scots language -- Variation -- Scotland -- Glasgow; Scots language -- Dialects -- Scotland -- Glasgow; Speech and social status -- Scotland -- Glasgow; English language -- Discourse analysis; Urban dialects -- Scotland -- Glasgow; Discourse analysis; Sociolinguistics; Glasgow (Scotland) -- Social conditions; Glasgow (Scotland) -- Languages; Electronic books